2020
DOI: 10.1109/access.2020.2995795
|View full text |Cite
|
Sign up to set email alerts
|

MILP-Based Differential Cryptanalysis on Round-Reduced Midori64

Abstract: Mixed integer linear programming (MILP) model was presented by Sun et al. at Asiacrypt 2014 to search for differential characteristics of block ciphers. Based on this model, it is easy to assess block ciphers against differential attack. In this paper, the MILP model is improved to search for differential trails of Midori64 which is a family of lightweight block ciphers provided by Banik et al. at Asiacrypt 2015. We find the best 5-round differential characteristics of Midori64 with MILP-based model, and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Similarly, 15 superpoly equations are chosen where α = α 1 (as there are |S (4,0,64) | − 1 = 15 different values of φ, excluding the instances where φ = α 1 ), whereas one superpoly equation is chosen where α = α 2 . This also results in 2 3 .16 = 2 7 encryptions.…”
Section: Application Of Side-channel Cube Attack S On Craftmentioning
confidence: 96%
See 2 more Smart Citations
“…Similarly, 15 superpoly equations are chosen where α = α 1 (as there are |S (4,0,64) | − 1 = 15 different values of φ, excluding the instances where φ = α 1 ), whereas one superpoly equation is chosen where α = α 2 . This also results in 2 3 .16 = 2 7 encryptions.…”
Section: Application Of Side-channel Cube Attack S On Craftmentioning
confidence: 96%
“…Note that two different values of α are used here such that 16 equations, 15 superpoly equations are chosen such that γ = γ 1 (as there are |S (4,0,64) | − 1 = 15 different values of φ, excluding the instances where φ = γ 1 ), whereas only one superpoly is chosen where γ = γ 2 . As a result, this yields 2 3 .16 = 2 7 encryptions. Finally, following the same rule, the superpoly equation in Observation 4 requires |S (4,0,64) | = 16 different values of φ and two different values of φ such that 1 , 2 , ∈ S (4,0,64) .…”
Section: Application Of Side-channel Cube Attack S On Craftmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors have shown that the differential property of modular addition with one constant input is illustrated with fewer number of linear inequalities input to the MILP solver compared to the common case. Hongluan Zhao et al [23] improved the search for differential trails of Midori64 given by Banik et al [16] by using MILP technique. They have given a better 5-round differential characteristics of Midori64 with the MILP-based model.…”
Section: Organization Of the Papermentioning
confidence: 99%
“…Over the years, many lightweight block ciphers have been developed inclusive of RoadRunneR [6], RECTAN-GLE [7], SAFER-Fermat [8], SKINNY [9], BORON [10], SPECK [11], PCB [12], Simeck [13], Midori [14], Loong [15], LRBC [16], and GIFT [17]. Two main foundation structures of lightweight block ciphers are the Feistel networks and Substitution-Permutation Network (SPN) structures.…”
Section: Introductionmentioning
confidence: 99%